PKM Pelatihan Pengelolaan Arsip Berbasis Komputer Bagi Pegawai Kantor Kepala Desa Sampali Kec. Percut Sei Tuan Kab. Deli Serdang Sumatera Utara - Ferry Fachrizal (Jurnal Abdimas HAWARI : Jurnal Pengabdian Kepada Masyarakat, 2021)
Community service activities are one of the tridharma of higher education. This service is one of the efforts of the Medan State Polytechnic to carry out the Tridarma of Higher Education to contribute science and technology to the community. Based on this, the Medan State Polytechnic submitted a proposal for community service activities at the Sampali village office, Kec. Percut Sei Tuan Kab. Deli Serdang, North Sumatra. The purpose of this service is to provide reinforcement in the form of briefing on making computer-based archive management regarding correspondence, both incoming letters, outgoing letters and village head decrees to the staff (village apparatus) of Sampali Village, especially basic village administrative documents so that an electronic filing system is created that good and orderly. Strengthening by rejuvenating this type of document is expected to provide provisions for village apparatus staff about the benefits of documents that are organized and managed to facilitate the implementation of excellent service to the community, especially data processing for solving problems that will be faced in community service.